2018
DOI: 10.1089/mdr.2017.0310
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Thermotolerant Campylobacter Species Isolated from Humans, Food-Producing Animals, and Products of Animal Origin: A Worldwide Meta-Analysis

Abstract: The objective of this meta-analysis was to summarize available information on the prevalence of antimicrobial-resistant Campylobacter species in humans, food-producing animals, and products of animal origin. A number of multilevel random-effect meta-analysis models were fitted to estimate mean occurrence rate of antimicrobial-resistant thermotolerant Campylobacter and to compare them throughout the years and among the species, food-producing animals (i.e., bovine, pigs, broilers, hen, goat, and sheep), country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
4
21
1
Order By: Relevance
“…These findings were in agreement with that previously reviewed in many studies (Saleha, 2002;Sáenz et al, 2000;Aarestrup and Engberg, 2001;Taremi et al, 2006). In contrary, C. coli showed a higher prevalence of antimicrobial resistance than C. jejuni by Signorini et al (2018) In this study, Campylobacter isolates were more sensitive to ciprofloxacin which is in agreement with McDermott et al (2002) and Moore et al (2005) who stated that ciprofloxacin was the drug of choice for empirical therapy of bacterial food borne diarrhea, including that caused by Campylobacter. In addition, Kassa et al (2007) found that C. jejuni, C. coli and C. lari isolated from food animals were sensitive to chloramphenicol and ciprofloxacin.…”
Section: Resultssupporting
confidence: 93%
“…These findings were in agreement with that previously reviewed in many studies (Saleha, 2002;Sáenz et al, 2000;Aarestrup and Engberg, 2001;Taremi et al, 2006). In contrary, C. coli showed a higher prevalence of antimicrobial resistance than C. jejuni by Signorini et al (2018) In this study, Campylobacter isolates were more sensitive to ciprofloxacin which is in agreement with McDermott et al (2002) and Moore et al (2005) who stated that ciprofloxacin was the drug of choice for empirical therapy of bacterial food borne diarrhea, including that caused by Campylobacter. In addition, Kassa et al (2007) found that C. jejuni, C. coli and C. lari isolated from food animals were sensitive to chloramphenicol and ciprofloxacin.…”
Section: Resultssupporting
confidence: 93%
“…e antimicrobials to which resistance was high included AMP, TET, ERY, and TET. e findings concur with the reports from other studies in both LMICs and high-income countries showing an increment in the number of Campylobacter strains resistant to most of the antimicrobials used in treating human campylobacteriosis [118][119][120]. e increase in resistance to most antimicrobial agents and emergence of MDR isolates could be associated with extensive use of antimicrobials not only as therapeutic agents for human infections [20] but also for prophylaxis and growth promotion in animal husbandry [68].…”
supporting
confidence: 89%
“…ese may cause differences within and between countries and certainly limit comparability with data reported in other parts of the world. e resistance to TET was comparable with the findings reported from Poland [121] and the USA [122] and the pooled estimate prevalence worldwide (94.3%) [120]. is resistance International Journal of Microbiology may be due to wide use of tetracycline in both human and veterinary medicine [20].…”
supporting
confidence: 83%
“…Interestingly, in recent years there has been an increase in the use of antimicrobials in animal breeding systems. The type of antimicrobial used, as well as the frequency and dose applied in animal feed may explain, at least partially, the prevalence of Campylobacter in food‐producing animals and the emergence of antimicrobial resistance in TC (Lévesque, Frost, & Michaud, ; Luber, Wagner, Hahn, & Bartelt, ; Signorini et al, ; Silbergeld, Graham, & Price, ; Wieczorek & Osek, ; Zbrun et al, ). The relatively stable prevalence of TC is accompanied by a gradual increase in the proportion of isolates resistant to antimicrobials, a phenomenon that became more evident in the last decade (Wieczorek & Osek, ).…”
Section: Discussionmentioning
confidence: 99%